Modeling of Processes in the Field of IT Education Implemented with the Use of Remote Technologies - Kuptsov, M. I.; Kuptsov, I. M.; Yablochnikov, S. L.; Yablochnikova, I. O.; Dzobelova, V. B. (Systems of Signals Generating and Processing in the Field of on Board Communications (Online), 2022)
High rates of scientific and technological progress determine the constant increase in demand in the labor market for highly qualified specialists, primarily those engaged in professional activities using IT. In modern conditions, the most relevant skill for graduates of higher educational institutions is the ability to adapt to dynamic changes and improve the information and communication technologies themselves and the means of their implementation. Accordingly, this leads to a significant modernization of the sphere of higher education and the totality of educational processes. In particular, approaches to quality assessment and ways to adequately determine its level are changing. The authors in this article propose to effectively assess the quality of modern education, using mathematical models developed by them. These models are synthesized by the authors based on the theory of fuzzy sets. Which, in turn, allows us to generalize a number of qualitative and quantitative criteria. And, consequently, to ensure the adaptation of models for the implementation of educational processes depending on a variety of identifiable factors. The results of the research carried out by the authors of this article can be very useful for a wide range of representatives of various communities of participants in socio-economic relations.